Challenges and opportunities in cell expansion for cultivated meat - Hauser, Michelle; Zirman, Amit; Rak, Roni; Nachman, Iftach (Frontiers in Nutrition, 2024)
The cultivation of meat using in vitro grown animal stem cells offers a promising solution to pressing global concerns around climate change, ethical considerations, and public health. However, cultivated meat introduces an unprecedented necessity: the generation of mass scales of cellular biomaterial, achieved by fostering cell proliferation within bioreactors. Existing methods for in vitro cell proliferation encounter substantial challenges in terms of both scalability and economic viability.Within this perspective, we discuss the current landscape of cell proliferation optimization, focusing on approaches pertinent to cellular agriculture. We examine the mechanisms governing proliferation rates, while also addressing intrinsic and conditional rate limitations. Furthermore, we expound upon prospective strategies that could lead to a significant enhancement of the overall scalability and cost-efficiency of the cell proliferation phase within the cultivated meat production process.By exploring knowledge from basic cell cycle studies, pathological contexts and tissue engineering, we may identify innovative solutions towards optimizing cell expansion.